Spatial modeling of discontinuity intensity - Challenges and considerations - Cepuritis, P.; Villaescusa, Ernesto (2013)
It is generally understood that discontinuity intensity can control a number of rock mass characteristics, such as rock mass strength and rock mass modulus, and influence rock mass response and behavior. Three-dimensional modeling can provide useful insights into the spatial variability of rock properties, however, there still are a number of aspects that hinders its full and comprehensive inclusion into rock mechanics applications. In contrast to traditional spatial modeling, where parameters are typified by scalar values (e.g. grade, density, etc.), one-dimensional discontinuity linear intensity parameters are vector variables and are unique to the borehole's orientation. The validity of spatial modeling of one-dimensional discontinuity linear intensity is therefore dependent on both the sampling direction and the degree of rock mass anisotropy. This paper describes some of the difficulties and considerations in the spatial modeling of discontinuity intensity from one-dimensional data. The paper also presents a three-dimensional test method to spatially quantify the degree of rock mass anisotropy. The method also allows practitioners to identify regions of the rock mass that have been isotropically sampled by drilling and where the spatial modeling of discontinuity intensity may be confidently applied. Copyright 2013 ARMA, American Rock Mechanics Association.